Development of ANFIS model and machinability study on dry turning of cryo-treated PH stainless steel with various inserts. Issue 6 (26th April 2017) - Palanisamy, D.; Senthil, P.
ABSTRACT: This present investigation deals about the machinability comparison of cryogenically treated 15-5 PH stainless steel with various cutting tools such as uncoated tungsten carbide, cryogenic-treated tungsten carbide and wiper geometry inserts. Cryo-treated PH stainless steel is considered as the work material in this investigation and experimental trials were performed under dry turning condition. The machinability aspects considered for evaluation are cutting force ( F z ), surface roughness ( R a ) and tool wear. The outcomes of experimentation reveal that the tungsten carbide inserts which are cryogenically treated provide improved performance in machining while comparing with conventional and wiper geometry inserts at all machining conditions. The measured cutting force and the observed flank wear were less for the cryo-treated inserts. However, wiper tool produces a better surface finish during machining. An artificial intelligence decision-making tool named Adaptive Neuro Fuzzy Inference System has been evolved to determine the relation among the considered input machining variables and output measures, namely cutting force and surface roughness of the machined surface. An analysis has been performed to compare the results obtained from developed models and experimental results.